Notary's Responsibility for Making Deed of Statement Related to Sale and Purchase Deed Containing Nominee Element - Putri, Sekar Rizqi Triroosa; Kusumadara, Afifah; Sjafi'i, R. Imam Rahmat (Institut Agama Islam Negeri Curup, 2024)
Notaries have the authority to make authentic deeds and are obliged to provide legal counseling related to deed making. However, there are notaries who provide legal counseling unethically, providing shortcuts without adequate consideration, which can lead to disputes and involve notaries in cases of Sale and Purchase Deeds Containing Nominee Elements. This is contrary to the Basic Agrarian Law (UUPA) and the Notary Position Law (UUJN), which prohibit foreign nationals from owning land titles in Indonesia and require notaries to act honestly and safeguard the interests of all relevant parties. Such actions are considered to violate the law and ethics of the notary profession. The method used is normative juridical research, to identify problems related to the Responsibility of Notaries for Making Statement Deeds Related to Sale and Purchase Deeds Containing Nominee Elements and will be analyzed based on legislation etc. The brief conclusion obtained from the results of this research is that Law Number 2 of 2014 concerning the Position of Notary stipulates that notaries who violate the rules will be subject to administrative sanctions, such as written warnings, temporary dismissal, honorable dismissal, and dishonorable dismissal. In addition, in civil law, notaries who cause losses to other parties due to violations may be subject to sanctions in the form of reimbursement of costs, compensation, and interest according to Article 84 of the Notary Position Law. These violations can cause the deed made by the notary to be degraded, only have evidentiary power under the hand, or be null and void.